Modified Mini-laparoscopic Surgery Optimized the Laparoscopic Decortication of Renal Cyst - Chen, Wei; XU, Zhi-Bing; XU, Lei; Cang, Chen; Guo, Jian-Ming (Urology Journal, 2019)
Purpose: This study was to introduce the modified mini-laparoscopic surgery for renal cyst and investigate its advantages on operative time, cosmetic effect and pain reduction by comparison with laparo-endoscopic single site surgery (LESS) and conventional laparoscopic surgery. Methods and patients: Between May 2015 and October 2018, 140 consecutive patients with benign renal cyst underwent laparoscopic decortication of renal cyst. Of which, 48 cases were in mini-laparoscopic surgery group (M group), 56 cases in LESS group and 36 cases in conventional laparoscopic surgery group (C group). The operative time, blood loss, visual analog scale (VAS) and Scar Cosmesis Assessment and Rating (SCAR) Scale was recorded. Results: The mean operative time in M group (26.08±7.70 min) and C group (28.56 ± 7.99 min). was significantly less than that in LESS group (47.32 ±10.53 min) (P < 0.01). Mean blood loss did not differ between the 3 groups (P > 0.05). Mean VAS pain scores in M group were significantly lower than that of LESS group and C group on postoperative day (POD) 1 and 3 (P < 0.01). The SCAR scale of POD 30 in C group (6.25 ± 1.0) was significantly higher than that in M group (0.77 ± 0.59) and LESS group (0.98 ± 0.70). The postoperative course was uneventful with no morbidity within 1to 6 months of follow-up. Conclusion: Modified mini-laparoscopic decortication of renal cyst have more comprehensive advantages comparing with LESS and conventional laparoscopic surgery. It is convenient and offered significant cosmetic benefit and reduced incisional pain.